Implementation of a comprehensive intervention focused on hospitalized patients with HIV by an existing stewardship program: successes and lessons learned. (April 2021) - Roshdy, Danya; McCarter, Maggie; Meredith, Jacqueline; Jaffa, Rupal; Hammer, Katie; Santevecchi, Barbara; Rozario, Nigel; Campbell, Jamie; Leonard, Michael; Polk, Christopher
Background: Several national organizations have advocated for inpatient antiretroviral stewardship to prevent the consequences of medication-related errors. This study aimed to evaluate the impact of a stewardship initiative on outcomes in people with HIV (PWH). Methods: A pharmacist-led audit and review of adult patients admitted with an ICD-10 code for HIV was implemented to an existing antimicrobial stewardship program. A quasi-experimental, retrospective cohort study was conducted comparing PWH admitted during pre- and post-intervention periods. Rates of antiretroviral therapy (ART)-related errors and infectious diseases (ID) consultation with linkage to care were evaluated through selection of a random sample of patients receiving ART in each period. Length of stay (LOS) and mortality were assessed by analyzing all admissions in the post-intervention period. Clinical outcomes including LOS, 30-day all-cause hospital readmission, and in-hospital and 30-day mortality in the post-intervention group were stratified by patients not on ART, on ART at admission, and started on ART as a result of the intervention. Results: A total of 100 patients in the pre-intervention period and 103 patients in the post-intervention period were included to assess ART-related errors and linkage to care. A reduction in errors (70.0 versus 25.7%, p  < 0.001) and increased linkage to care (19.0 versus 39.6%, p  < 0.01) were demonstrated. Of 389 admissions during the post-intervention period, 30-day mortality rates were similar between PWH on ART at admission and those initiated on ART during admission (5% versus 8%, respectively), but less than those not on ART (21%). A longer LOS was observed in the patients started on ART during admission (5 days if ART started during admission versus 3 days if not started during admission, p  < 0.01). Conclusions: This interdisciplinary intervention was successful in reducing inpatient ART-related errors and increasing ID consultation with linkage to care among PWH.